ANALISIS PENGUKURAN KINERJA KEUANGAN BERBASIS WEB DENGAN METODE ANALISIS RASIO KEUANGAN (STUDI KASUS: KSPPS BMT AL-FALAH) - Amroni Amroni; Muhammad Hatta; Shifa Alfiandra Erlina (Universitas Catur Insan Cendekia (CIC) Cirebon, 2017)
Abstract Saving-loan and financing sharia cooperative BMT AL-FALAH is an financial institution that operating in saving-loan field. Although every transaction has been operated by computerized system, the system hasn’t been able to serve an representation of cooperative’s financial condition. It because there is still no financial report analysis, so that cooperatives doesn’t know about how its financial condition, is it good or not. Because of their ignorance, cooperatives will not able to determine policies in certain periode. Therefore every financial institution, especially cooperative need an analysis process to measure how well its financial performance, so that management will able to determine the policies easier in order to improve management performance. Web Basis Application Financial Reports Analysis to Measure Financial Performance with Ratio Analysis Method was made to make the treasurer easier to analyze financial reports with ratio analysis method, so that the treasurer will able to serve an sharper and more complete financial information that contain in Analysis report. Beside that, this application also was made to make the manager easier in making decision especially in financial aspect. This application was created using PHP Hypertext Preproccessor programming language, and MySQL software as data storage media. Based on the description above, we can conclude that this application is an application that process finished data (balance sheet and income summary). With creating this application, we expect that it would serve cooperative an financial condition representation and also give an sharper and more complete financial information that will make the manager easier in to determine the best policies that needed in order to improve management and financial performance. Keywords: financial report analysis, ratio analysis, financial reports, cooperative.